DESIGN AND DEVELOPMENT OF MULTI-INPUT SENSOR ALGORITHM FOR AUTONOMOUS UNDERWATER VEHICLE (AUV) APPLICATIONS - Mohd Aras, Mohd Shahrieel; Jamaluddin, Muhamed Herman; Kasdirin, Hyreil Anuar (2010)
This project is to design and develop a multi-input algorithm of sensors for Autonomous Underwater Vehicle (AUV) applications which is having high performance automated detection and monitoring on underwater application or for surveillances and defense application. The monitoring and detection will be based on multi-input received from the intelligent and active vision and sensors implemented in the AUV. The sensors implemented in AUV such as vision system, hydrophone system and sonar system. The new design of vision system for AUV with the implementation of wireless camera, whereby, produce clearer image. The ultrasonic sensor is a main device to transmit and receive the signal from the obstacle. The ultrasonic sensor will be combined to the ultrasonic circuit. Hydrophone is an underwater microphone which with the help of pressure impulses of acoustic waves converts them into electrical signals which in further are used for communication. It was designed to be used underwater for recording or listening to underwater sound.